Joint IMF-WBG Staff Note : DSSI Fiscal Monitoring Update. (Policy Papers; Policy Paper ;, 2021)
The COVID-19 pandemic put significant pressures on fiscal accounts during 2020 through a contraction of revenues and increased spending needs to tackle the pandemic and its economic fallout. In response to these pressures, the countries benefitting from the Debt Service Suspension Initiative (DSSI) have faced difficult choices to reprioritize spending, especially capital spending, even as they allowed higher overall fiscal deficits. This note summarizes the findings from the update of the fiscal monitoring system for the COVID-19 Debt Service Suspension Initiative (DSSI). The DSSI was endorsed by the G20 Finance Ministers on April 15, 2020 and extended twice in October 2020 (until end-June 2021) and April 2021 (until end-2021). During May-December 2020 (the first phase), 43 countries participated, and 42 countries have formally requested their participation in the initiative during January-June 2021 (the second phase, as of July 30, 2021).